2018
DOI: 10.1016/j.jacc.2018.06.072
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Hyaluronan Metabolism in Acute Coronary Syndrome

Abstract: HYAL2 and CD44v6 splicing variants seem to play an important role in ACS, in particular when associated with plaque erosion. After further validation, HYAL2 might represent a potentially useful biomarker for the noninvasive identification of this mechanism of coronary instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…17,22,23) Recent clinical study found that enhanced hyaluronidase 2 and CD44v6 splicing variant expression in circulating peripheral blood mononuclear cells was prevalent in ACS patients presenting with PE. 24) Intriguingly, based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, we know that the predicted target genes of miR-3667-3p participate in the "proteoglycans in cancer" pathway. In addition, a positive correlation between circulating miR-3667-3p levels and fibrotic plaque constituent that mainly consists of collagen, proteoglycans, and SMCs has been observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…17,22,23) Recent clinical study found that enhanced hyaluronidase 2 and CD44v6 splicing variant expression in circulating peripheral blood mononuclear cells was prevalent in ACS patients presenting with PE. 24) Intriguingly, based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, we know that the predicted target genes of miR-3667-3p participate in the "proteoglycans in cancer" pathway. In addition, a positive correlation between circulating miR-3667-3p levels and fibrotic plaque constituent that mainly consists of collagen, proteoglycans, and SMCs has been observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The sub-endothelial matrix of eroded plaques contains abundant hyaluronan and its binding partner versican [5]. The recent observation that OCT-defined plaque erosion patients have increased HYAL2 (the enzyme responsible for degrading high-molecular-weight hyaluronan to its proinflammatory 20-kDa isoform) and the hyaluronan receptor CD44v6 adds weight to a potential causal relationship [9]. Hyaluronan and versican may regulate vascular inflammation in atherosclerosis [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…For example, plaque rupture occurs on inflamed and lipid-rich plaques with a greater degree of calcification. In contrast, sites of erosion generally occur on smooth muscle cell-and proteoglycan-rich plaques, specifically containing high levels of versican and the glycosaminoglycan hyaluronan and low levels of biglycan, containing few inflammatory leucocytes [1,[5][6][7][8][9]. In addition, the thrombi overlying eroded plaques display more organisation, indicative of a longer existence, potentially up to 7 days before presentation of clinical symptoms [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, an in vivo experiment found that hyaluronidase 2 (HYAL2) and its receptor mediated the recruitment of polymorphonuclear (PMNc) leukocytes and the formation of thrombi in plaque erosion was induced by ow perturbation. 7 However, whether systemic HA changes in STEMI is unknown. Moreover, the difference in circulating HA expression between plaque rupture and erosion has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%